Metaphors For Trauma: A Cross‐Cultural Qualitative Comparison in Brazil, India, Poland, and Switzerland. Issue 5 (10th June 2020) - Rechsteiner, Karin; Maercker, Andreas; Heim, Eva; Meili, Iara
Abstract: The concept of psychological trauma implies that people experiencing traumatic stress are wounded, thus relating to the metaphor of a physical injury. Although this notion is widely accepted by clinicians and researchers in mental health, there is evidence of a broad range of metaphorical idioms for extremely aversive experiences or catastrophic events across different cultures. In this ethnopsychological study, we aimed to investigate and contrast culturally shared metaphors for trauma among four distinct cultural groups: two indigenous communities (Pitaguary from Brazil, Adivasis from India) and two rural communities (mountain villagers of Gondo, Switzerland; the Lemko ethnic minority in Poland). The communities in Brazil and in Poland were marked by historical trauma, and the communities in India and Switzerland each suffered from a natural disaster. Semistructured interviews that focused on metaphors shared within each community were conducted with key informants and laypersons (Brazil: N = 14, India: N = 28, Poland, N = 13, Switzerland: N = 9). We conducted separate metaphor analyses, then cross‐culturally contrasted the findings from the four samples. Across the four cultural groups, we found similar metaphorical concepts of trauma related to bodily processes, such as shock, burden, and wound . Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Metáforas en Trauma: Una Comparación Transcultural Cualitativa en Brasil, India, Polonia, y Suiza METÁFORAS PARA EL TRAUMA DESDE UNA PERSPECTIVA CULTURAL El concepto de trauma psicológico implica que las personas que experimentan estrés traumático están heridas, relacionándose así con la metáfora de una lesión física. Aunque esta noción es ampliamente aceptada por médicos e investigadores en salud mental, existe evidencia de una amplia gama de modismos metafóricos para experiencias extremadamente aversivas o eventos catastróficos en diferentes culturas. En este estudio etnopsicológico, nuestro objetivo fue investigar y contrastar las metáforas del trauma compartidas culturalmente entre cuatro grupos culturales distintos: dos comunidades indígenas (Pitaguary de Brasil, Adivasis de India) y dos comunidades rurales (habitantes de las montañas de Gondo, Suiza; la minoría étnica Lemko en Polonia). Las comunidades de Brasil y Polonia estuvieron marcadas por un trauma histórico, y las comunidades de India y Suiza sufrieron cada una un desastre natural. Se realizaron entrevistas semiestructuradas, que se enfocaron en metáforas compartidas dentro de cada comunidad, con informantes clave y personas de la comunidad (Brasil: n = 14, India: n = 28, Polonia, n = 13, Suiza: n = 9). Realizamos análisis de metáforas por separado, luego contrastamos transculturalmente los hallazgos de las cuatro muestras. En los cuatro grupos culturales, encontramos conceptos metafóricos similares de trauma relacionados con procesos corporales, como "shock", "carga", y "herida". Además, se identificaron expresiones metafóricas específicas de la cultura para cada grupo. Los resultados de este estudio sugieren que, aunque las metáforas incorporadas comparten algunas características universales, las expresiones específicas de la cultura reflejan fuertemente los contextos socioculturales e históricos, indicando aproximaciones potenciales para la adaptación cultural de las intervenciones clínicas. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐19‐0316.R2_Rechsteiner Metaphors on Trauma: A Cross‐Cultural Qualitative Comparison in Brazil, India, Poland, and Switzerland Traditional Chinese 標題: 創傷隱喻:巴西、印度、波蘭及瑞士的跨文化質性比較 撮要: 心理創傷的概念意味著經歷過創傷壓力的人等同受了傷, 因此帶有肉體受傷的隱喻。雖然此說法受到臨床治療師與研究學者廣泛認同, 但亦有證據顯示, 不同文化對極度厭惡的經歷或災難事件有林林總總的隱喻慣用語。是次民族心理學研究的目的, 旨在探查及對比四個不同的文化群體之間共通的創傷隱喻。這些群體包括:兩個原住民社群 (巴西的比塔哥里 (Pitaguary) 族與印度的阿迪瓦西族), 及兩個鄉村社群 (瑞士剛多 (Gondo) 村的村民及波蘭蘭克的少數民族) 。巴西和波蘭的社群經歷過歷史創傷;而印度和瑞士的社群則經歷過一次天災。我們對社群中提供資料的人士及一般居民進行半結構性面談, 探討每個社群中共通的隱喻 (巴西: n = 14, 印度: n = 28, 波蘭: n = 13, 瑞士: n = 9)。我們進行分開的隱喻分析, 再對四組樣本進行跨文化對比, 並發現四個文化群體均有與身體反應有關、相近的創傷隱喻, 例如「休克」、「負擔」及「傷口」。此外, 每個群體亦有與其文化特殊相關的隱喻表達。是次研究結果顯示, 雖然不同文化使用的隱喻有一些共通特徵, 但文化特殊的表達方式強烈反映社會文化及歷史的背景, 反映可能有潛在方法因應不同文化而對臨床干預作出相應的調節。 Simplified Chinese 标题: 创伤隐喻:巴西、印度、波兰及瑞士的跨文化质性比较 撮要: 心理创伤的概念意味着经历过创伤压力的人等同受了伤, 因此带有肉体受伤的隐喻。虽然此说法受到临床治疗师与研究学者广泛认同, 但亦有证据显示, 不同文化对极度厌恶的经历或灾难事件有林林总总的隐喻惯用语。是次民族心理学研究的目的, 旨在探查及对比四个不同的文化群体之间共通的创伤隐喻。这些群体包括:两个原住民社群 (巴西的比塔哥里 (Pitaguary) 族与印度的阿迪瓦西族), 及两个乡村社群 (瑞士刚多 (Gondo) 村的村民及波兰兰克的少数民族) 。巴西和波兰的社群经历过历史创伤;而印度和瑞士的社群则经历过一次天灾。我们对社群中提供数据的人士及一般居民进行半结构性面谈, 探讨每个社群中共通的隐喻 (巴西: n = 14, 印度: n = 28, 波兰: n = 13, 瑞士: n = 9)。我们进行分开的隐喻分析, 再对四组样本进行跨文化对比, 并发现四个文化群体均有与身体反应有关、相近的创伤隐喻, 例如「休克」、「负担」及「伤口」。此外, 每个群体亦有与其文化特殊相关的隐喻表达。是次研究结果显示, 虽然不同文化使用的隐喻有一些共通特征, 但文化特殊的表达方式强烈反映社会文化及历史的背景, 反映可能有潜在方法因应不同文化而对临床干预作出相应的调节。